The Economy of Western Xia A Study of 11th to 13th Century Tangut Records - Shi, Jinbo (Brill, 2021)
This is the first introduction to the economic history of the Tangut Empire (1038-1227). Built on a wealth of economic data and evidence, it studies the economic lives and activities, laws and institutions, trade and transactions in the "Great State White and High". It interprets primary sources written in the mysterious Tangut cursive script: taxes, registers, and contracts, alongside archives, chronicles, and law codes. By weaving Song, Liao, and Jin materials with Khara-Khoto, Wuwei, and Dunhuang manuscripts into a historical narrative, the book offers a gateway to the outer shape and inner life of the Western Xia (Xixia) economy and society, and rethinks the Tanguts' influence on the Hexi Corridor and the Silk Road. Readership: Historians interested in East and Inner Asia in the 11th-13th centuries, historians of medieval China: late Tang, Five Dynasties, Liao, Song, Jin Dynasties; Scholars interested in Dunhuang and Tangut studies.